HUBUNGAN ANTARA PERHATIAN ORANGTUA DENGAN PERILAKU PROSOSIAL ANAK 3-4 TAHUN DI KAMPUNG LUBUK GAMBIR KENAGARIAN KAPELGAM - Fauza Nabila; Setiawati; Alim Harun Pamungkas; Rembulan Catra Banyu Biru (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the relationship between parental attention and the prosocial behavior of children aged 3–4 years in Kampung Lubuk Gambir, Kenagarian Kapelgam. The background of this research is based on the phenomenon that some children still show a lack of prosocial behaviors such as sharing, helping, and cooperating, which are suspected to be related to the level of parental attention in daily life. This research is a quantitative study using a descriptive-correlational design. The population consisted of 30 children and their parents, with a sample of 23 respondents selected through random sampling. Data were collected using a Likert-scale questionnaire measuring two variables: parental attention (X) and children’s prosocial behavior (Y). The data were analyzed descriptively and inferentially using the Pearson Product Moment correlation test. The results showed that parental attention was in the high category, with most respondents choosing “often” (40.87%) and “always” (25.43%). Meanwhile, children’s prosocial behavior was in the moderate category, with most respondents choosing “sometimes observed” (48.12%) and “often observed” (36.81%). The inferential analysis obtained an r-value of 0.623 with t-count = 3.65 > t-table = 2.080 at a 5% significance level. This indicates a positive and significant relationship between parental attention and the prosocial behavior of children aged 3–4 years. In conclusion, the higher the parental attention given, the higher the level of prosocial behavior shown by the children. These findings support Bandura’s Social Learning Theory and Bowlby’s Attachment Theory, which emphasize that parental attention and emotional involvement play a crucial role in shaping children’s empathy and social concern from an early age.